THE EFFECTIVENESS OF THE NOBANGAN LEARNING MODEL BASED ON THE TRADITIONAL GAME OF KAILI TRIBE ON MATHEMATICS LEARNING OUTCOMES OF STUDENTSIN CLASS IV SD INPRES BINANGGA - Mawar Sari; Azizah Azizah; Yasri Z (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effectiveness of the Nobangan learning model based on the traditional game of the Kaili tribe on the mathematics learning outcomes of fourth grade students of SD Inpres Binanngga. This type of research is an experimental quantitative research using the Quasi Experiment method with the Noneequivalent Control Group Design. The subjects in this study were the fourth grade students of SD Inpres Binanngga, totaling 21 people. There were 11 experimental class students and 10 control class students. Data collection was carried out using research instruments in the form of Multiple Choice Tests, and data analysis using prerequisite tests, namely normality tests and homogeneity tests and hypothesis testing using Independent sample t-test tests which were analyzed using SPSS Statistics version 25. Based on the results of this study showed a significant value of 0.002 0.005 then accept the Ha hypothesis and reject Ho, meaning that the Nobangan learning model is effectively used in improving students' mathematics learning outcomes.Keywords: Nobangan Learning Model, Kaili Tribe Traditional Game, Mathematics Learning Outcomes